Penerapan Analitycal Hierarchy Process Pada Sistem Pendukung Keputusan Pemilihan Laptop - Luthfi Alfuadi Lutfy; Nur Hidayat; Selviana Yunita; Elika Thea Kirana (Universitas Sains dan Teknologi Komputer, 2023)
Laptops are very necessary for students in lectures. However, choosing a laptop for student needs is not easy. A way to help college students decide which laptop is right for their needs is to use a decision support system. The process used by DSS is the Analytical Hierarchy Process or AHP. shows that the Asus Vivobook Ultra 15 laptop is the first priority for students with a total score of 0.1243, the HP 250 G8 laptop is the second priority with a total score of 0.0951, and the Lenovo V14 G2 laptop is the last priority with a total score of 0.0823 for students. Based on the review and assessment of the previous chapter, the following conclusions can be drawn:1. Making DSS for laptop selection can be pursued with an analytical Hiarakiya process that ensures the criteria and weights are calculated systematically. 2. The process of analytic hierarchy, which is a decision support procedure for solving various multi-criteria decision problems, can also be used to solve the laptop selection problem.